2019
DOI: 10.1530/erc-19-0278
|View full text |Cite
|
Sign up to set email alerts
|

The molecular genetic make-up of male breast cancer

Abstract: Male breast cancer (MBC) is extremely rare and accounts for less than 1% of all breast malignancies. Therefore, clinical management of MBC is currently guided by research on the disease in females. In this study, DNA obtained from 45 formalin-fixed paraffin-embedded (FFPE) MBCs with and 90 MBCs (52 FFPE and 38 fresh-frozen) without matched normal tissues was subjected to massively parallel sequencing targeting all exons of 1943 cancer-related genes. The landscape of mutations and copy number alterations was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 89 publications
(100 reference statements)
1
24
0
Order By: Relevance
“…The N-terminus interacts with CTIP/RBBP8. We found two frameshift hotspots in reported COSMIC mutations (R466Gfs*18 [ 71 , 74 , 75 , 81 , 82 , 90 , 91 , 92 , 93 ] and R551Gfs*8 [ 71 , 74 , 92 , 94 , 95 , 96 , 97 , 98 ]) that introduce termination codons in the middle region between the BRCT domains and the MRE11 interaction domains ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminus interacts with CTIP/RBBP8. We found two frameshift hotspots in reported COSMIC mutations (R466Gfs*18 [ 71 , 74 , 75 , 81 , 82 , 90 , 91 , 92 , 93 ] and R551Gfs*8 [ 71 , 74 , 92 , 94 , 95 , 96 , 97 , 98 ]) that introduce termination codons in the middle region between the BRCT domains and the MRE11 interaction domains ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The RAD50 K722 residue is characterized primarily by the Rfs*14 (c.2165del) frameshift [ 75 , 80 , 81 , 82 , 99 ] but a K722R (c.2165A>G) substitution and a different K722Gfs*5 (c.2164_2165del) frameshift have also been detected [ 71 ]. The NBS1/NBN R466Gfs*18 (c.1396del) is the most often occurring mutation [ 71 , 74 , 75 , 81 , 82 , 90 , 91 , 92 , 93 ] with R466K (c.1397G>A) [ 100 ] and R466Kfs*5 (c.1396dup) [ 92 ] detected sporadically. Similarly, the NBS1/NBN R551Gfs*8 (c.1651del) mutation is also the most represented [ 71 , 74 , 92 , 94 , 95 , 96 , 97 , 98 ], but an R555K (c.1652G>A) substitution [ 101 ] and a different R551Kfs*5 (c.1651dup) [ 71 ] frameshift have also been identified.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with a recent study of DNA sequencing analysis on 1943 cancer-related genes in 135 patients with male breast cancer, which demonstrated differences in the genomic landscape between male and female breast cancers. Somatic mutations in homologous recombination deficiency-related genes were more prevalent in male breast cancer compared to female breast cancer, whereas TP53 somatic mutations were less frequent [36]. Currently, it becomes clear that some important markers in breast cancer biology can play a different role in male compared to female breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to population-based studies about MBC, the percentages of ER+ MBC are reported to be about 90% or more than 95% [ 6 , 7 ]. The percentages of PR + MBC ranged from 60 to 90%, generally to be about 80.0% [ 7 9 ]. The rates of HER2 positive among MBC differ from the testing methods and the different region.…”
Section: Introductionmentioning
confidence: 99%